First Report of Colletotrichum nymphaeae Causing Pear Anthracnose in China - Zhang, Xiaoyan; Ou, Jiwang; Wang, Xueqian; Wu, Hao; He, Ying; Hong, Ni; Wang, Guoping; Wang, Liping (Plant disease, 2025)
China is a major producer of pears in the world and anthracnose is the most important disease, which may include fruit rot and early defoliation, and further brings enormous economic losses. In August of 2023, a sudden outbreak of anthracnose disease, ranging from 70% to 90% disease incidence, occurred on fruits of Pyrus pyrifolia (Burm.f.) Nakai in 200 acres of three pear orchards at Baiyi town, Guiyang city, Guizhou Province of China. Thirty diseased fruits were randomly collected three pear orchards, i.e., 10 fruits from each, and transported to the laboratory for analysis. The symptoms showed dark brown lesions that extended rapidly causing sunken fruit rot lesions harboring orange conidial clumps. To identify the pathogen, three from the 10 diseased fruits per orchard were used for isolation. Small tissue pieces of diseased fruits were disinfected and rinsed twice with 75% alcohol and sterile water, placed on a potato dextrose agar (PDA), and cultured at 25℃ in a dark (Fang, 1998). Ten isolates with same colony morphology were obtained. Two isolates, GZ-3 and GZ-5, were randomly selected for further analysis. The GZ-3 and GZ-5 isolates grew on PDA plates at an average daily growth rate of 0.8~1.0 cm/d in the darkness at 25℃. The colonies were white to gray on the front side and greyish-green to orange on the reverse side. The conidia were hyaline, smooth, nonseptate, and fusiform, measuring 9.0-19.2×2.5-6.1 μm, with the average mean of 13.9±2.2×4.4±0.9 μm (n=50) for GZ-3, and the size of 9.5-15.4×2.3-4.8 μm, with average size of 13.1±1.5×3.7±0.5 μm (n=50) for GZ-5, respectively. The morphological characteristics of the GZ-3 and GZ-5 colonies were consistent with those of Colletotrichum acutatum complex (Damm et al. 2012). To confirm the pathogenicity, the 6 × 106 mL-1 spore suspension of GZ-3 and GZ-5 were inoculated on healthy P. pyrifolia (Burm.f.) Nakai fruits using the non-invasive spray method, while sterile water was used to inoculate control fruits. The fruits inoculated with the two isolates exhibited dark brown spots in the early stage of the disease, then the lesions expanded to rot and produced orange conidia. GZ-3 and GZ-5 were reisolated from the fruits, fulfilling Koch's postulates. The internal transcribed spacer (ITS) rDNA, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), actin (ACT), chitin synthase 1 (CHS-1) and β-tubulin (TUB2) were partially amplified using the primers designed previously (Weir et al. 2012) and sequenced. The above five gene sequences from GZ-3 showed 99.63% to 100% identity with those of GZ-5, respectively. The GZ-3 sequences were deposited in GenBank (ACT: PP825836; TUB2: PP825837; CHS-1: PP825838; GAPDH: PP825839; ITS: PP821112). The sequence alignment was performed based on the concatenated sequence of ACT-TUB2-CHS-1-GAPDH-ITS. A phylogenetic tree, constructed using the Neighbor-Joining method with bootstrap replication 2200 bootstrap alignments in MEGA11.0, showed GZ-3 and GZ-5 clustering with reference C. nymphaeae isolates. Based on the obtained morphological characterization and phylogenetic analysis results, GZ-3 and GZ-5 were identified as C. nymphaeae. Currently, 12 Colletotrichum species causing pear anthracnose have been reported in China (Fu et al. 2019). To our knowledge, this is the first report of C. nymphaeae causing pear anthracnose in the country. The findings are significant for a quick monitoring and control of pear anthracnose.